Planktonic and benthic foraminifera carbon and oxygen stable isotope records of IODP Site 339-U1387 (Gulf of Cadiz) for the interval of Marine Isotope Stage (MIS) 42 to MIS 46 (1.34-1.41 Ma) - Voelker, Antje H L (PANGAEA, 2025)
This dataset includes the G. bulloides and the epibenthic foraminifera stable isotope data along the revised splice of IODP Site U1387 (Gulf of Cadiz) for the interval from Marine Isotope Stage (MIS) 42 to MIS 46 (1.34-1.41 Ma). The data from MIS 43 to MIS 46 is published in Trotta et al. (2025), whereby the data for the older part from MIS 46 to MIS 48 is available under Voelker et al. 2022. The additional data from MIS 42 to mid-MIS 43 will be published in a future manuscript by Anna R. Kicsi, Giulia Molina and Antje H.L. Voelker. The epibenthic foraminifera stable isotope data reflects conditions in the upper Mediterranean Outflow Water.
Keywords: benthic d13C; benthic d18O; IODP Site U1387; Mediterranean outflow; Planktic d18O; Stable carbon and oxygen isotopes